Dictionary of the Theater: Terms, Concepts, and Analysis - Pavis, Patrice (Toronto University of Toronto Press, 1998)
Patrice Pavis is one of France's most brilliant academics and a leading expert internationally in the theory of theatre. Dictionary of the Theatre is an English translation of Pavis's acclaimed Dictionnaire du théâtre, now in its second printing in France.This encyclopedic dictionary includes theoretical, technical, and semiotic terms and concepts. Alphabetical entries range from 'absurd' to 'word scenery' and treat the reader to a vast panoply of theatre and theory. The extended discussions are supported by useful examples drawn from the international repertoire of plays and playwrights, both classic and contemporary. The Foreword is by Marvin Carlson.This dictionary is remarkably well integrated, partly because of its excellent system of cross-referencing, but also because it represents the vision and scholarship of a single, recognized authority. There is no other source like it available and it will be warmly welcomed by the English-language theatre world.
Keywords: Theater; Theater history; Dictionary